Nursing guidelines for ostomized patients: Integrative review (Research, Society and Development, 2021)
Introduction: Newly ostomized patients find it very difficult to adapt to their new body shape and also present social problems. The role of the nurse as a health educator for patients, family members and caregivers is an inherent competence in care practice. Objective: To describe the scientific evidence available in the literature on nursing guidelines for ostomy patients. Methods: This is an integrative literature review, from 2016 to 2021, in the Lilacs and BDENF databases. The following descriptors were used in the bases: “Ostomy”, “Nursing”, “Health Education”. For the crossing of descriptors, a protocol with Boolean AND is used. As inclusion criteria, articles available in the databases and with full text and free access and studies available in Portuguese were selected. Exclusion criteria were editorials from journals, letters to the editor and studies that did not address the theme of the work. Results: After filtering based on the defined flowchart, nine articles were selected according to established criteria. After reading and analyzing the articles, three thematic categories emerged, which were: "Health education and the role of nurses facing the ostomy patient", "Health education approaches to promote self-care and rehabilitation of the ostomy patient" and “Strategies and technologies for permanent education of teams about ostomies”. Conclusion: it is concluded that the health education of professional nursing professionals is of fundamental importance for the promotion of self-care for ostomy patients.